38.0k views
4 votes
Given that 2x + 3y - 10 = 0 and 3x = 2y - 11, calculate the value of ( x - y ).

User Rocket
by
5.4k points

2 Answers

2 votes
Step-by-step: x=2/3 y - 11/3
now we know the value of x, so we substitute it into the equation
2(2/3 y - 11/3) + 3y -10= 0
Y=4
x=2/3 x 4 - 11/3
x= -1

-1 - 4 = -5
User Peter Dang
by
5.0k points
3 votes

Answer:

x - y = - 5

Explanation:

Given the 2 equations

2x + 3y - 10 = 0 ( add 10 to both sides )

2x + 3y = 10 → (1)

3x = 2y - 11 ( subtract 2y from both sides )

3x - 2y = - 11 → (2)

Multiplying (1) by 3 and (2) by - 2 and adding will eliminate the term in x

6x + 9y = 30 → (3)

- 6x + 4y = 22 → (4)

Add (3) and (4) term by term to eliminate the x- term

13y = 52 ( divide both sides by 13 )

y = 4

Substitute y = 4 into either of the 2 equations and evaluate for x

Substituting into (1)

2x + 3(4) = 10

2x + 12 = 10 ( subtract 12 from both sides )

2x = - 2 ( divide both sides by 2 )

x = - 1

Thus

x - y = - 1 - 4 = - 5

User Andrew Harry
by
5.2k points